THE UTEROCERVICAL ANGLE AS AN ADDITIONAL ULTRASOUND MARKER FOR PREDICTION OF PRETERM BIRTH - O. V. Astaf'eva; I. V. Karyakina; E. A. Aslanyan; N. V. Micheeva (Кубанский научный медицинский вестник, 2018)
Aim. The study was conducted to determine the informative significance of the uterocervical angle for prediction of preterm birth using the ultrasound cervicometry at 16-20 weeks of pregnancy.Materials and methods. 340 pregnant women aged 20-35 were examined at 16-20 weeks of pregnancy using the ultrasound cervicometry and by measuring the uterocervical angle. The interrelation analysis of the pregnancy outcome (preterm birth or birth at term) was carried out depending on the cervical length and the uterocervical angle value at 16-20 weeks of pregnancy. Results. Preterm birth before 37 weeks occurred in 32 patients (9.4%). The average value of the uterocervical angle at 16-20 weeks was 104,2±0,9 degrees in case of preterm birth and 92,3±2,7 degrees in case of birth at term. While analyzing the interrelation of the uterocervical angle value and preterm birth, it was found that the frequency of preterm birth with the uterocervical angle of >105º was 81.2% and 16,9% in case of birth at term (OR 21,333 [CI 8,363-54,418], p<0,05).Conclusion. The uterocervical angle is a prognostically significant criterion for predicting preterm birth with the sensitivity of 81.3% and the specificity of 83.1%. The diagnostic effectiveness of the test was 83,1%.